Progress of fermentation methods for bio-succinic acid production using agro-industrial waste by Actinobacillus succinogenes - Dwini Normayulisa Putri; Muhamad Sahlan; Ludovic Montastruc; Michel Meyer; Stéphane Negny; Heri Hermansyah (Energy Reports, 2020)
Production of bio-succinic acid through microbial fermentation using agro-industrial waste has been observed extensively. Large scale production is now being considered since bio-succinic acid has broad range application in several industries including agricultural, food, chemical, metal, and pharmaceutical industry as a precursor, ion chelator, and or additive agent. One of promising microbes able to produce bio-succinic acid in large amount and recognized for industrial production is Actinobacillus succinogenes. However, several factors still need to be considered in order to optimize the fermentation performance. Therefore, this paper aims to review the progress of fermentation methods and discuss the fermentation strategy focused on the influences of different carbon sources, nitrogen sources, pH regulator, and fermentation configuration to the fermentation parameters including concentration, productivity and yield of bio-succinic acid. As a result, combinations of several fermentation strategies are needed to be performed to realize an efficient and effective bio-succinic acid industry.
Keywords: 330; Agro-industrial waste; Bio-succinic acid; Fermentation strategies